Exploring EFL Teachers’ Self-Efficacy and Readiness for Student-Centered Assessment Approaches - Aidah Nur Hafizah; Ira Maisarah (MASI Mandiri Edukasi, 2026)
The shift in assessment to a more student-oriented approach means that EFL teachers need not only to learn about the idea but also to feel they can implement it in their everyday practice. This study aims to examine how EFL teachers build their self-efficacy and readiness in using student-oriented assessment, particularly the application of self-assessment in writing classes. A qualitative approach was used in collect data; semi-structured interviews with three teachers across various school levels were conducted. The results indicate that, despite teachers' awareness of the pedagogical advantages of self-assessment, several challenges remain, including students' low competence, inconsistent institutional support, and inadequate training. This study concludes that teacher readiness is greatly influenced by a combination of psychological factors, such as self-confidence and self-perceived competence, and contextual factors that shape their scope of action. For further research, a broader study covering schools with different conditions, or one that combines classroom observations, is needed to obtain a more complete picture of student-centered assessment practices.